CSF1R-mediated myeloid cell depletion shifts the ratio of motor cortical excitatory to inhibitory neurons in a multiple system atrophy model - Gauer, Carina; Battis, Kristina; Schneider, Yanni; Florio, J. B.; Mante, M.; Kim, H. Y.; Rissman, R. A.; Hoffmann, Alana; Winkler, Jürgen (Experimental Neurology, 2024)
Motor cortical circuit functions depend on the coordinated fine-tuning of two functionally diverse neuronal populations: glutamatergic pyramidal neurons providing synaptic excitation and GABAergic interneurons adjusting the response of pyramidal neurons through synaptic inhibition. Microglia are brain resident macrophages which dynamically refine cortical circuits by monitoring perineuronal extracellular matrix and remodelling synapses. Previously, we showed that colony-stimulating factor 1 receptor (CSF1R)-mediated myeloid cell depletion extended the lifespan, but impaired motor functions of MBP29 mice, a mouse model for multiple system atrophy. In order to better understand the mechanisms underlying these motor deficits we characterized the microglial involvement in the cortical balance of GABAergic interneurons and glutamatergic pyramidal neurons in 4-months-old MBP29 mice following CSF1R inhibition for 12 weeks. Lack of myeloid cells resulted in a decreased number of COUP TF1 interacting protein 2-positive (CTIP2+) layer V pyramidal neurons, however in a proportional increase of calretinin-positive GABAergic interneurons in MBP29 mice. While myeloid cell depletion did not alter the expression of important presynaptic and postsynaptic proteins, the loss of cortical perineuronal net area was attenuated by CSF1R inhibition in MBP29 mice. These cortical changes may restrict synaptic plasticity and potentially modify parvalbumin-positive perisomatic input. Collectively, this study suggests, that the lack of myeloid cells shifts the neuronal balance toward an increased inhibitory connectivity in the motor cortex of MBP29 mice thereby potentially deteriorating motor functions.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Colony-stimulating factor 1 receptor; Excitation-inhibition balance; GABAergic interneurons; Microglia-neuron-interaction; Motor cortex; Multiple system atrophy; PLX5622; Pyramidal neurons